AN ISOTOPIC AND PETROLOGIC STUDY OF CALCIUM-ALUMINUM-RICH INCLUSIONS FROM CO3 METEORITES - Russell S.S.; Huss G.R.; Fahey A.J.; Wasserburg G.J.; Greenwood R.C.; Hutchison R. (My University, 1998)
We have studied the mineralogy and petrology of 229 calcium-aluminum-rich inclusions (CAIs) from ten CO3 meteorites of petrologic types 3.0–3.7. Subsets of these inclusions were measured by ion probe for magnesium, calcium, and titanium isotopes and REE abundances. Most CAIs from CO3 meteorites fall into three major types: (1) melilite-rich inclusions, which also contain spinel/hercynite, perovskite, and occasionally hibonite; (2) spinel-pyroxene inclusions; and (3) hibonite-hercynite inclusions. In addition, several isolated hibonite grains, two grossite (CaAl_4O_7) bearing CAIs, two hibonite-fassaite microspherules, and one anorthite-spinel-pyroxene inclusion were found. CAIs from CO3 meteorites exhibit all of the REE patterns commonly seen in inclusions from CV3 and CM2 chondrites. Most exhibit evidence of ^(26)AI, and many have inferred (^(26)AI/^(27)AI)_o ≈ 5 × 10^(−5). The relative abundances of different types of CAIs in CO3 chondrites differ from those in CV3 and CM2 chondrites. CAIs in CO3 chondrites have experienced considerable secondary alteration, both before and after accretion. Signatures of nebular alteration include Wark-Lovering rims and the high Fe contents in spinels from all hibonite/hercynite inclusions. Occasionally, melilite and anorthite show evidence of nebular alteration to feldspathoids and pyroxene. The magnesium-aluminum systematics of some melilite-rich inclusions were apparently disturbed prior to final accretion of the parent body. Parent body alteration is indicated by correlations between CAI characteristics and the petrologic type of the host meteorite. Spinel in melilite-rich and coarse-grained spinel-pyroxene inclusions becomes more Fe rich, with the development of relatively homogeneous hercynitic spinel (∼50–60 mol%) in CAIs from metamorphic grades >3.4. Perovskite has been converted to ilmenite in types >3.4. Melilite-rich inclusions are abundant in CO3.0–3.3 meteorites, rare in 3.4 meteorites, and absent meteorites of types 3.5–3.7; melilite-rich CAIs are probably replaced by inclusions rich in feldspathoids, pyroxene, and Fe-rich spinel. Isotopic disturbance of the magnesium-aluminum systematics may be more severe in higher petrologic types. Hibonite seems to be unaffected by this level of metamorphism. Three isotopically unusual inclusions were found. One single-crystal hibonite, Isna SP16, has a REE pattern strongly depleted in Ce and Y, (^(26)AI/^(27)AI)_o = (2.4 ± 0.3) × 10^(−5), and mass fractionated calcium (F_(Ca) = +12 ± 2‰/amu), but no resolvable nuclear anomalies in neutron-rich calcium isotopes. The REE pattern, which is thought to reflect nebular conditions, and mass-fractionated calcium, indicative of evaporation, are similar to those of the FUN inclusion, HAL, and related hibonites, indicating similar formation conditions. The absence in Isna SP16 of the nuclear anomalies observed in HAL and the difference in (^(26)AI/^(27)AI)_o between HAL and Isna SP16 indicate that the processes that produced HAL-type hibonites operated on diverse materials. Two hibonite-bearing microspherules, Colony SP1 and ALH82101 SP15, exhibit nearly flat REE patterns with negative europium anomalies and slightly negative δ^(26)Mg. ALH82101 SP15 has resolved excesses of ^(48)Ca and ^(50)Ti. These characteristics are similar to those of previously described microspherules from Murchison and Lance, implying that the microspherules formed via a single process from related, but not identical source materials.